1998
DOI: 10.1097/00003246-199806000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Mortality is increased by procalcitonin and decreased by an antiserum reactive to procalcitonin in experimental sepsis

Abstract: These results demonstrate that increased ProCT exacerbates mortality in experimental sepsis, whereas neutralization of ProCT increases survival. Thus, ProCT, in addition to being an important marker of severity of systemic inflammation and mortality, is an integral part of the inflammatory process and directly affects the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
176
1
18

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(202 citation statements)
references
References 18 publications
7
176
1
18
Order By: Relevance
“…This result was consistent with the experimental data: the procalcitonin time course is thought to be closely dependent on bacterial load and the host response to microbial challenge. 36 Procalcitonin kinetics may offer a solution for the dilemma regarding positive sputum cultures (interpretation of colonization or infection) and guide in determining the appropriate duration of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…This result was consistent with the experimental data: the procalcitonin time course is thought to be closely dependent on bacterial load and the host response to microbial challenge. 36 Procalcitonin kinetics may offer a solution for the dilemma regarding positive sputum cultures (interpretation of colonization or infection) and guide in determining the appropriate duration of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…| IL-1b serum concentration over a 72-hour-period of one horse with an acute colic (Nylen et al 1998, Wagner et al 2002, Martinez et al 2001 (Gogos et al 2000). Beim Menschen bilden IL-1b, IL-6 und TNFa auch den Stimulus für eine Hyperprocalcitoninämie (Redl et al 2000, Redl et al 2001, Whang et al 2000.…”
Section: Abb3unclassified
“…It has also been reported that injection of proCT augments the mortality of hamsters suffering from sepsis (Nylen et al 1998). It would be of great interest to examine whether pro-sCTs have similar effects in rainbow trout, even though the amino acid homology between fish and mammalian proCTs is less than that between their CTs.…”
Section: Discussionmentioning
confidence: 99%